(untitled) (ACME, 2021)
The paper aims to be an investigation into the anti-romantic engagement that characterized Bernardo Bellini’s (1792-1876) literary production for about thirty years, going through the Classicist/Romantic quarrel (1816), the short season of the «Conciliatore», the diatribes aroused in the second half of the Twenties, from Vincenzo Monti’s Sermone sulla mitologia and from the Lombardi alla prima crociata by Tommaso Grossi, up to the early Forties, when, in Turin, Bellini collided with the young Giovanni Prati. In each of these controversies, the polygrapher demonstrated a lively and often unscrupulous polemic vein, claiming (sometimes with belated fury) the reasons for his faction, also through an instrumental involvement of distinguished exponents of the recent Italian poetic tradition, such as Vincenzo Monti, Ugo Foscolo and Giacomo Leopardi.